Net revenue and downstream flow impact trade-offs for a network of small-scale hydropower facilities in California. (4th February 2019) - Craig, Michael; Zhao, Jin; Schneider, Gia; Schneider, Abe; Watson, Sterling; Stark, Greg
Abstract: Deployment of small-scale hydropower, which generally ranges in capacity from 1-10 MW, may partly depend on its ability to mitigate environmental concerns while generating sufficient revenues. In this paper, we quantify net revenue and downstream flow impact trade-offs of a cascading series of 36 small-scale hydropower facilities under consideration for development in Northeast California. To do so, we develop a net-revenue-maximizing optimization model that determines hydropower operations while capturing key technical and river network constraints. We find that significantly constraining maximum discharges from each facility largely eliminates downstream flow impacts but negligibly changes the 36 facilities' combined operations and net revenues. Thus, we find a negligible trade-off between net revenues and downstream impacts in our study system, suggesting small-scale hydropower can contribute to decarbonization efforts while limiting local environmental impacts on downstream flows at little economic cost.